VALUE RELATIONS OF PARTICIPANTS - CONDITION OF EFFECTIVE PEDAGOGICAL PARTNERSHIP - Shtefan, Maryna; Vorozhbit-Gorbatyuk, Victoria; Volkova, Yana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Accessibility and openness of information and reference bases with spreading of the distal format of training is determined by the main advantage during both stages of the empirical research. The level of satisfaction is higher than in directions: Information formatting, simplicity of algorithmic submission and clear content of tasks with artistic, productive activity.The article makes it clear that parity through equal accessibility contributes to the harmonization of educational goals and objectives for the formation of valuable attitudes of the participants of the educational process is achieved in a constructive dialog. Mobility of educational interaction in the system "Teacher – pupils, parents of the child". The study confirmed that parity presupposes the use of the information offered and available in the network through educational cooperation. It is important to establish a strong consistent connection for detailed discussion of hot topics, avoiding the diversity of the proposed primary sources, personalization of educational experience gained during the distance execution of specific educational tasks due to individual possibilities (knowledge of language, ability to work with different content, etc.). Parity provides stable open access to the necessary educational information, cognitive activity, which is clearly observed during use of distance learning tools. This reveals the possibility of reflexia as an element of the logical structure of parity of educational interaction. Careful attitude to the position, opinions of each participant of the educational process, equality in the right to express a personal vision of one or another element of the educational and methodical complex will help to form valuable attitudes.